Cancer : the emperor of all maladies [videorecording (DVD)] - Burns, Ken, 1953-; Mukherjee, Siddhartha; Herrmann, Edward, 1943-2014 (PBS Distribution, 2015)
Presents a history of cancer, from ancient times to the present day. Includes stories of contemporary patients and examines the latest scientific research which might indicate that we are on the brink of a lasting cure.